'Superior Seedless' grapevine grafted on three rootstocks grown on calcareous soil under diluted brackish water irrigation. III. Stomatal resistance. Issue 3 (3rd July 2018) - Qrunfleh, Issam M.
ABSTRACT: Grapevine rootstocks that can be irrigated with diluted brackish water without any adverse effects on grapevine performance are a suitable approach for areas suffering scarce water resources. Stomatal resistance of 'Superior Seedless' grafted on three rootstocks, irrigated with different levels of diluted brackish water, was evaluated and correlated with some growth parameters. 'Superior Seedless' grafted on 1103P showed less stomatal resistance as compared to 110R and 41B. Ratios of 'Superior Seedless' leaf fresh and dry weights to leaf area were not significantly different among the rootstocks. However, 'Superior Seedless' grafted on 1103P showed better performance regarding chlorophyll content, shoot length and growth following bud break.